Facile and highly selective deprotection of tert-butyldimethyl silyl ethers using sulfated SnO2 as a solid catalyst - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Rode, Chandrashekhar V. (Synthetic Communications, 2008)
Highly selective deprotection of tert-butyldimethylsilyl ethers at room temperature has been described using sulfated SnO2 as an efficient solid catalyst.
Keywords: deprotection; sulfated SnO2; TBDMS ethers

Functionalization of single-walled carbon nanotubes with azides derived from amino acids using click chemistry - Kumar, Indresh; Rana, Sravendra; Rode, Chandrashakher V.; Cho, Jae Whan (Journal of Nanoscience and Nanotechnology, 2008)
Single-walled carbon nanotubes (SWCNTs) were chemically functionalized with amino acid-based moieties. The covalent functionalization of alkyne-derived SWCNTs with well defined azides derived from amino acids was accomplished through Cu(I)-catalyzed Huisgen [3+2] dipolar cycloaddition click chemistry. Transmission electron microscopy, Raman spectroscopy, and infrared spectroscopic measurements confirmed the functionalization of SWCNTs by organic molecules derived from amino acids, and the resulting material showed some good solubility in the organic solvents such as tetrahydrofuran, CH2Cl2, and CHCl3.
Keywords: Amino acids; Carbon nanotubes; Click chemistry; Functionalization